2022
DOI: 10.1002/adma.202203246
|View full text |Cite
|
Sign up to set email alerts
|

Activatable Cancer Sono‐Immunotherapy using Semiconducting Polymer Nanobodies

Abstract: Despite the great promises of sonodynamic therapy (SDT) in combination cancer therapy, its clinical applications are hindered by the “always‐on” pharmacological activities of therapeutic agents and the lack of efficient sonosensitizers. Herein, the development of semiconducting polymers as efficient sonosensitizers and further development of sono‐immunotherapeutic nanobodies (SPNAb) for activatable cancer sono‐immunotherapy are reported. Conjugation of anti‐CTLA‐4 antibodies onto the polymer nanoparticles thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 42 publications
0
50
0
Order By: Relevance
“…1 O 2 has been recognized as a main cause of US-mediated death of tumor cells. [42,43] Accordingly, 2′,7′-dichlorofluorescein diacetate (DCFH-DA) was utilized to determine the intracellular ROS based on the generated green fluorescence signals from 2′,7′-dichlorofluorescein (DCF) converted from DCFH-DA in the presence of ROS. [44,45] Figure S10a, Supporting Information, revealed that the negative green fluorescence signals detected from the control cells (without treatment) were indicative of low concentrations of intracellular ROS.…”
Section: In Vitro Anti-colon Cancer Activity Of Nmsmentioning
confidence: 99%
“…1 O 2 has been recognized as a main cause of US-mediated death of tumor cells. [42,43] Accordingly, 2′,7′-dichlorofluorescein diacetate (DCFH-DA) was utilized to determine the intracellular ROS based on the generated green fluorescence signals from 2′,7′-dichlorofluorescein (DCF) converted from DCFH-DA in the presence of ROS. [44,45] Figure S10a, Supporting Information, revealed that the negative green fluorescence signals detected from the control cells (without treatment) were indicative of low concentrations of intracellular ROS.…”
Section: In Vitro Anti-colon Cancer Activity Of Nmsmentioning
confidence: 99%
“…The combination of SDT with other cancer treatments has shown great potential as a new tumor treatment strategy. 21,109 In this section, we broadly summarize and discuss several SDT-based combination therapy strategies, including chemotherapy, photodynamic therapy (PDT), chemodynamic therapy (CDT), immunotherapy, and photothermal therapy (PTT) (Table 3).…”
Section: Sonodynamic Therapy-based Combination Therapymentioning
confidence: 99%
“…[26] A variety of NIR-II absorption or NIR-II fluorescence agents, such as gold nanomaterials, copper sulfide nanomaterials, and conjugated polymers (CPs), have been developed as NIR-II excitation multifunctional phototheranostic agents. [27] In comparison with metal nanomaterials, organic CPs possess the salient advantages of outstanding biocompatibility and ease of processability, [28] and hence, they have generated tremendous interest among NIR-II PTT/chemotherapy, NIR-II PTT/gas therapy, and NIR-II PTT/CDT researchers. [29] Nevertheless, there are two major challenges for CP-based phototheranostics that compromise their clinical applicability.…”
Section: Introductionmentioning
confidence: 99%